The Importance of Disaster Response Awareness for Tourism Object Managers in West Sumatra - Retnaningtyas Susanti; Pande Made Kutanegara; heriani . (The Tourism, Heritage and Recreation Sport Center, Universitas Negeri Padang, 2019)
Disaster is one of the main threats to tourism around the world. There are various kinds of disasters, ranging from terrorist attacks; social, cultural and political issues; disease outbreaks, and natural phenomena (floods, landslides, tsunamis, earthquakes and storms). One of the disasters being experienced by all tourism managers in West Sumatera is earthquakes. Disasters can occur and threaten the sustainability of a tourist attraction. The threat of disaster has an impact on tourist visits, so an effort is needed to prepare tourism managers to deal with it. The tourism industry is an economic activity that is highly dependent on image, when a tourist attraction fails to face a disaster, tourists are reluctant to visit the place. The methods used are interviews, observations, and literature studies that can help answer research questions. The key informants in this study were members of the tourism management in West Sumatra Province. The results showed that each tourist destination has a different threat of disaster from other areas, so the response required by the manager is also different. In the case of the earthquake, the response to the disaster cannot be overcome by all tourist destination managers, all experiencing the same conditions. Developed and developing tourist destinations need the same amount of time to deal with this disaster. The recommendation of this study is the importance of understanding disaster response by all tourist destination managers, so that the required recovery period is not too long, and tourism can return to its normal operation.